Classroom Management Problems Faced by Pre-service Teachers of English Education Program in Senior High Schools - Rizki Fajar Jayadi; Sugeng Susilo Adi (Fakultas Ilmu Budaya, Universitas Brawijaya, 2022)
This research was intended to find out the kinds of problems, and how pre-service teachers deal with the problems relating to classroom management. The subject were students pre-service teachers who teach English to students in Senior High School. This study use quantitative descriptive method where the data of this study were gathered through the interview and questionnaire as the instruments of data collection. This study involved 56 students of English Education Program in FIB UB who conducted pre service teachers in Senior High School in academic year 2019/2020 as subject of the study. The participants were chosen by using random sampling technique in which the sample was chosen randomly, without considering any specific categorization both female and male. Specifically, the participants were chosen by considering their experience while pre-service teaching in Senior High School. This study used survey design as the method. The data was gathered through a questionnaire adapted from [1] Akarshu 2012, [2]Cezmi and Toprak (2013) and [3]Luo, Bellow and Grady (2000), the questionnaires about the problems relating in classroom management in learning process with a total of 21 statements. The researcher only takes 16 statements and translate to English. The research found 17 problems relating to classroom management which were additional item from the respondents and divided into two categories. They are; the classroom discipline and classroom participation. The five main problems are: 1) students make too much noise in class, 2) students lack of interest in lesson, 3) students inability to understand the lesson, 4) students not paying attention and 5) students come late to class. Moreover, dealing with the second research question about how the pre-service teachers deal with the problems, the writer found the SFS (students who try to find solutions) pre fer to solve the problems by developing teacher-students communication in the classroom.Keywords: classroom management, pre service, student teachers